Normativitas dan historitas dalam Islam - Makiyyah, Zahrotul; Ghozi, Ahmad; Azhar, Muhammad Helmi Al; Suparto, Fajar Dwi (Maliki Interdisciplinary Journal, 2024)
This journal discusses two main approaches in Islamic studies, namely the normative and historical procedures, and their have an effect on in knowledge the history and present day history of Islam. Islam as a found out faith demands authenticity with out distortion, however ought to additionally be able to accommodate progressivity in human life. The normative technique, which emphasizes admire for traditional values and the sanctity of texts, often produces a criminal-formal and rigid expertise. In evaluation, the ancient method emphasizes the massive meaning in the back of spiritual texts, permitting Islamic research to be more modern and in line with the dynamics of life. Figures consisting of Fazlur Rahman and Amin Abdullah are imperative to this debate, highlighting the significance of reinterpreting religious teachings in keeping with the context of the technology to make clear the issue of human religiosity. this text makes use of library studies methods to gather and examine applicable resources. the main findings show that despite the fact that the normative approach remains dominant, a historical method is more and more wished in the context of the plurality of global Muslims to understand Islamic history more accurately in accordance with to be had information and statistics.